An efficient injection protocol for Drosophila larvae - Soltani, Sattar; Huynh, Nhan; King-Jones, Kirst (Biology methods and protocols, 2024)
Intravenous injection provides a direct, rapid, and efficient route for delivering drugs or other substances, particularly for compounds with poor intestinal absorption or molecules (e.g. proteins) that are prone to structural changes and degradation within the digestive system. While Drosophila larvae represent a well-established genetic model for studying developmental and physiological pathways, as well as human diseases, their use in analyzing the molecular effects of substance exposure remains limited. In this study, we present a highly efficient injection method for Drosophila first- and second-instar larvae. Despite causing a slight developmental delay, this method achieves a high survival rate and offers a quick, easily adjustable protocol. The process requires 3–5 h to inject 150–300 larvae, depending on the microcapillary needle, microinjection system, and the compound being administered. As proof of concept, we compared the effects of injecting ferritin protein into Fer1HCH00451 mutant first instar larvae with those of dietary ferritin administration. Our results show that ferritin injection rescues Fer1HCH mutants, a result that cannot be achieved through dietary delivery. This approach is particularly valuable for the delivery of complex compounds in cases where oral administration is impaired or limited by the digestive system.